The effects of low frequency sound on the levels of activation - Kasprzak, Cezary (Archives of Acoustics, 2007)
The paper summarises the research data showing how low frequency sound affects the levelof activation in humans. Activation levels were measured with the use of the self-assessmentquestionnaire, known as the Activation-Deactivation Adjective Check List (AD ACL). The researchprogram involved three independent stages and three types of acoustic stimuli wereapplied. The acoustic stimulus applied in the first stage had frequency $f = 7$ Hz, sound pressurelevel SPL = 120 dB (HP). In the second stage participants were exposed to an acousticstimulus $f = 18$ Hz, sound pressure level SPL = 120 dB (HP). In the third stage a acousticstimulus was applied $f = 40$ Hz, sound pressure level SPL = 110 dB (HP). The exposuretime in each experiment was constant (20 min). Results indicate a statistically significantincrease of the deactivation – sleep effect following the low-frequency sound exposure.